A narrative review on the correlation between diabetic foot and sarcopenia - Sui, Yunpeng; Ma, Ya; Zhou, Kai; Liang, Rui; Liu, Xiaolei (Frontiers in Endocrinology, 2026)
Diabetic foot (DF) and sarcopenia are common complications in individuals with diabetes and are linked through a bidirectional and mutually reinforcing relationship. From a pathophysiological perspective, insulin resistance disrupts skeletal muscle metabolism, while diabetic neuropathy and peripheral arterial disease compromise muscle function and mobility, increasing susceptibility to DF. Persistent low-grade inflammation further promotes muscle wasting and worsens glycemic dysregulation, establishing a self-perpetuating cycle. The presence of sarcopenia is associated with a two- to three fold increased risk of DF and is linked to poorer outcomes, including delayed wound healing and a higher likelihood of amputation. In turn, disability and reduced mobility caused by DF accelerate muscle disuse and atrophy. Integrated management strategies, encompassing resistance training, adequate protein intake, optimized glycemic control, and proactive foot care, are essential to interrupt this cycle. Although emerging pharmacological agents that enhance muscle anabolism show promise, further clinical validation is required. A multidisciplinary approach is necessary to curb the reciprocal progression of these conditions and to improve clinical outcomes in affected patients.